Equitable access to land as a means of poverty reduction in rural china - Yan Hao (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
In China, as in many developing countries, poverty is primarily a rural phenomenon. Considerable efforts have been made over the last few decades to reduce poverty in China's rural areas; and indeed, the poverty rate in these areas has fallen from 30.7% in 1978 to 3.8% in 2009. This paper begins with a review of ancient Chinese texts on the importance of equitable access to land. In an agrarian economy, the issue of land distribution is critical not only to a country's economic prosperity but also to its political survival. After reviewing the achievements and failures of the Communist government's land policy introduced in the 1950s, I discuss the household contract system launched by the government in the early 1980s. Under the new system, the formerly collectively owned farmland was contracted out equally to villagers on a household basis, who hold the land in quasiprivate ownership. The policy ensuring farmers' equal access to land has profound political, economic, and social implications in today's China. Given the well-documented correlation between landlessness and rural poverty, the role of land security in reducing poverty in rural China should not be underestimated. However, this policy alone cannot eliminate poverty completely. Even when families are equally granted a piece of land, they may still suffer from poverty if the land cannot produce enough food or generate sufficient income. I enumerate a number of on-going anti-poverty programs at national and local level that supplement the policy on equitable access to land. While these supplementary programs are indeed important, China's experience shows that equitable access to land is an especially effective means to combat rural poverty.
Keywords: I38; P25; R52; 330; China; rural poverty; poverty reduction; Communist government; land policy; land distribution; developing countries; Ländliche Armut; Agrarboden; Bodenpolitik; Bodenreform; China